Blood heavy metals (arsenic, cadmium and lead) concentration and genetic polymorphism of glutathione S-transferase genes among adults in coastal area of Melaka, Malaysia - Mohd Noor, Farrah Atiqah; Mohd Elias, Saliza; Abu Bakar, Suhaili; Aris, Ahmad Zaharin; Md Zulkifli, Hamizah (UPM Press, 2022)
Introduction: Heavy metals exposure through the consumption of seafood are an environmental issue of concern. Biomonitoring of whole blood heavy metals concentration give an insight on the total internal body burden. The level of heavy metals of an individual are interrelated to the genetic polymorphism of glutathione S-tranferases (GSTs). This study aims to determine the association between blood arsenic (BAs), blood cadmium (BCd) and blood lead (BPb) concentration as reported in previous report and polymorphic variants of GST genes. Methods: Sixty three adult respondents were recruited along the coastal area of Melaka through purposive sampling in February 2016. Blood samples were collected through venipuncture procedure by certified personnel in EDTA tubes. The inductively coupled plasma- mass spectrometry (ICP-MS) instrumentation was used to analyse the blood heavy metals concentration. DNA was extracted from the whole blood samples. The polymorphic variants of GSTM1 and GSTT1 were analysed by multiplex polymerase chain reaction (PCR) and polymorphic variants of GSTP1 were analysed by polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP). Results: The BAs, BCd and BPb median (IQR) concentrations detected were 0.076 (0.059 – 0.107), 1.204 (0.670 – 2.094) and 0.076 (0.038-0.138) (µg/L) respectively. The prevalence of genetic polymorphism in GSTM1 and GSTT1 of 63.5% and 38.1% were observed. The number of respondents who have both deleted genes for GSTM1 and GSTT1 was 17 (27%). The frequency of genetic polymorphism in GSTP1 was 55.5%, in which 29 (46.0%) of the respondents were having the heterozygous (Ile/Val) polymorphism while the other 6 (9.5%) respondents were having the homozygous mutant (Val/Val). Conclusion: The polymorphic GST gene variations were not statistically linked to heavy metal concentrations. Respondents with the Val/Val genotype in GSTP1 and both GSTM1 and GSTT1 deletions, had a greater median of BAs and BPb